Staufen2-mediated RNA recognition and localization requires combinatorial action of multiple domains - Simone Heber (Nature Portfolio, 2019)
The Staufen family of RNA-binding proteins are conserved microtubule dependent mRNA transporter factors. Here the authors use biochemical and functional approaches to characterize the RNA-binding properties of mouse Staufen 2 and study the mRNA binding capacity of its two domains dsRBDs 1 and 2.